IDENTIFIKASI PENGGUNAAN ZAT PEWARNA SINTETIS PADA SAUS CABAI YANG DIPASARKAN DI PASAR TRADISIONAL DAYA - Thresia Dewi Kartini; zakaria zakaria; Fasa Novita Putri (Jurusan Gizi Poltekkes Kemenkes Makassar, 2017)
Background: Chilli is a plant that grows in certain seasons and easily damaged. There are several forms of processed chili such as the shape of semi-processed and processed forms own company, such as chili sauce. Things to consider in the process of making the chili sauce is food hygiene and safety, because it will affect the health of consumers. Consumer acceptance of a product may increase because of the color of the food. However, the food coloring food additives that require more scrutiny because sometimes the use is not in accordance with the recommended dosage or even use non-food dyes.Objectives: This research aim’s to identify the use of synthetic dyes in chili sauce sold in Makassar Traditional Markets Daya.Methods: This research is descriptive survey’s research. Identification of synthetic dyes obtained by Paper Chromatography Test. Readable identification results with UV light with a frequency of 254 and 366 nm.Results: The results showed that 4 chili sauce marketed in Traditional Markets Daya using synthetic dyes which allowed its use in Indonesia, namely sunset yellow, ponceau 4-R and tatrazine. In addition there is also the use of more than one type of synthetic dyes.Suggestion: Qualitatively chili sauce can be used, but further research is needed to see the levels of dye are added in it. Advised to relevant agencies to pay more attention and control of food products, both products that have been circulating as well as new products that will be circulated.Keywords: Synthetic dyes, Chili Sauce